Inversion asymmetry effect on quantum oscillations in 3-D crystals with Cnv symmetry - Ivchenko, V.V.; Sergeev, A.N.; Elnik, V.S.; Chuiko, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The peculiarities of quantum oscillations in bulk semiconductors with Cnv symmetry caused by the lack of their symmetry centre are considered. A quasi-qubic model is used for finding the magnetic levels. The algorithm for numerical calculating the levels in the presence of the tilted magnetic field is suggested. Numerical estimations are performed for Сd₃As₂ and Cd₃₋xZnxAs₂. It is shown that the most suitable conditions for observing the beating effect in these compounds are the high values of the electron concentrations and small angles between the direction of the magnetic field and crystal symmetry axis.